PENYULUHAN KELAS IBU HAMIL TENTANG STANDAR PELAYANAN ANTENATAL CARE TERPADU 10 T DI BPM ARNI WILAYAH KERJA PUSKESMAS BOTANIA KOTA BATAM - Mastikana, Indah; Mutiara, Sherly; Aditya; Kartika, Siti (Transpublika Publisher, 2022)
To reduce maternal mortality in Indonesia, one of the strategies is to provide antenatal care (ANC) services. According to statistics from health care institutions, particularly hospitals and maternal perinatal audits (AMP), 30 women died in 2017 at a rate of 105 per 100.000 live births. This number exceeds the 2016 figure of 97 per 100.000 births. The purpose of this activity is to ensure a healthy life and support the welfare of the mother and fetus, especially to prevent AKI and IMR. The method used is counseling in the local community and also during classes for pregnant women in certain midwife clinic areas. Based on the results of these activities, it was found that the mothers were very enthusiastic about the counseling. The new ANC approach which consists of components that discuss safe delivery planning, ANC communication approaches and family involvement of pregnant women can increase knowledge about ANC, especially knowledge about complications of pregnancy and safe delivery.